2017
DOI: 10.1093/nar/gkx214
|View full text |Cite
|
Sign up to set email alerts
|

Substrate preference of Gen endonucleases highlights the importance of branched structures as DNA damage repair intermediates

Abstract: Human GEN1 and yeast Yen1 are endonucleases with the ability to cleave Holliday junctions (HJs), which are proposed intermediates in recombination. In vivo, GEN1 and Yen1 function secondarily to Mus81, which has weak activity on intact HJs. We show that the genetic relationship is reversed in Drosophila, with Gen mutants having more severe defects than mus81 mutants. In vitro, DmGen, like HsGEN1, efficiently cleaves HJs, 5΄ flaps, splayed arms, and replication fork structures. We find that the cleavage rates f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 60 publications
3
24
0
Order By: Relevance
“…A previous study demonstrated that GEN1 initially binds the HJ as a monomer (34). Since we always observed the resolution within the lifetime of the GEN1-HJ complex, we propose that GEN1 monomer distorts the HJ and remains firmly bound until a dimer is formed and full resolution of the HJ takes place.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study demonstrated that GEN1 initially binds the HJ as a monomer (34). Since we always observed the resolution within the lifetime of the GEN1-HJ complex, we propose that GEN1 monomer distorts the HJ and remains firmly bound until a dimer is formed and full resolution of the HJ takes place.…”
Section: Resultsmentioning
confidence: 99%
“…The incision requires the coordination of two active sites contrary to a mechanism where a single nick takes place, followed by protein dissociation, reassociation, then counter nicking (33). The inactivity of GEN1 monomer on HJ is supported by the observation that GEN1 monomer binds HJs more tightly than its dimer and that excess HJ decreases the cleavage rate by sequestering the monomer from solution (34). Further evidence suggests that even with the decoupling of the two incisions, either by using an active subunit of the dimer associated with a catalytically inactive partner or a non-cleavable phosphorothioate cleavage site, the first incision still seems to require GEN1 dimerization (33).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The attained temporal resolution can be within microseconds to several milliseconds . Understanding how GEN1 binds the HJ, coordinates the two incisions, and ensures its full resolution have all been under intensive study 21,22,23,25,26,27,28,29,30 .…”
Section: Introductionmentioning
confidence: 99%
“…There was some indication of activity on other branched species, but the enzyme was most active on four-way junctions. By contrast, GEN1 from Drosophila was found to cleave a wider range of branched substrates ( 37 ), and significantly those studies were performed in the presence of K + ions. Given the importance of K + ions in the activity and structure of the other FEN/EXO family members we sought to re-examine both the protein structure and substrate range of Ct GEN1 in the presence of other monovalent ions.…”
Section: Introductionmentioning
confidence: 99%